2017
DOI: 10.1680/jgeot.17.t.037
|View full text |Cite
|
Sign up to set email alerts
|

Plant age effects on soil infiltration rate during early plant establishment

Abstract: Infiltration rate affects slope stability by determining the rate of water transport to potential failure planes. This note considers the influences of vegetation (grass and willow) establishment and root growth dynamics on infiltration rate, as related to establishing vegetation on bioengineered slopes. Soil columns of silty sand with and without vegetation were tested by constant-head infiltration tests at 2, 4, 6 and 8 weeks after planting. Infiltration rate increased linearly with plant age and below-groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 22 publications
9
72
0
2
Order By: Relevance
“…The fractal dimension of soil particle size had a strong positive correlation with the initial infiltration rate (R 2 = 0.9037) and the stable infiltration rate (R 2 = 0.9229). Thus, based on regression analysis, the correlation with the steady infiltration rate was stronger than with the initial infiltration rate, which is due to the fractal dimension of PSD reflecting the spatial filling capacity of soil based on the distribution of soil particles [35]. In other words, the smaller the soil particle diameter (i.e., clay, silt, and organic matter), the greater the spatial filling capacity of the soil, which corresponds to higher fractal dimension values of PSD.…”
Section: Correlation Between Fractal Dimension and Soil Infiltration mentioning
confidence: 97%
“…The fractal dimension of soil particle size had a strong positive correlation with the initial infiltration rate (R 2 = 0.9037) and the stable infiltration rate (R 2 = 0.9229). Thus, based on regression analysis, the correlation with the steady infiltration rate was stronger than with the initial infiltration rate, which is due to the fractal dimension of PSD reflecting the spatial filling capacity of soil based on the distribution of soil particles [35]. In other words, the smaller the soil particle diameter (i.e., clay, silt, and organic matter), the greater the spatial filling capacity of the soil, which corresponds to higher fractal dimension values of PSD.…”
Section: Correlation Between Fractal Dimension and Soil Infiltration mentioning
confidence: 97%
“…Note that (n -ua) and (ua -uw) is referred to as net normal stress and matric suction (s), respectively. When plant roots exist, the shear strength equation may be modified by adding a term so-called "root cohesion" (cr) in Eq (6), to account for the effect of mechanical root reinforcement: = • • (7) where kr is an empirical root-soil interaction factor that depends on root orientation and root breakage process, taken to be 0.318 for U. europaeus ; Ar is root-area ratio (RAR; ratio between cross-section area of roots crossing a shear plane and total area of the shear plane). Since the root tensile strength (defined by the final root diameter after dehydration) is a function of root water content (Fig.…”
Section: Shear Strength Equationsmentioning
confidence: 99%
“…The new diameter is also used to update the Ar in Eq. (7). Eventually, the shear strength of unsaturated soil due to the simultaneous changes of cr and Se can be estimated, via Eq.…”
Section: Soil-root Moisture Exchangementioning
confidence: 99%
“…Some studies (Table 1) showed an increase in water retention capability when plant roots are present in the soil (Scanlan & Hinz, 2010;Rahardjo et al, 2014;Leung et al, 2015;Ng et al, 2016a, b;Jotisankasa & Siririrattanachat, 2017), probably because of the blockage of soil pore space by roots (Buczko et al, 2007). However, some studies reported an opposite result Jotisankasa and Sirirattanachat, 2017), arguably because of the formation of soil cracks due to, for instances, repeated soil shrinkage, swelling and root decay and growth (Vergani & Graf, 2015;Ng et al, 2016a;Ni et al, 2017;Leung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%